Manajemen Cairan Pada Pasien Ketoasidosis Diabetik DM Tipe 2 Dengan Ketidakstabilan Kadar Glukosa Darah - Nurul Azmi Fauziyah; Sandra Pebrianti; Sri Hartati Pratiwi (Quantum Wellness : Jurnal Ilmu Kesehatan, 2024)
Diabetic ketoacidosis (DKA) is a life-threatening form of diabetes mellitus emergency. Rapid and appropriate management is needed to prevent worsening condition. Fluid management in DKA is important to improve tissue perfusion, correct electrolyte imbalance, reduce blood glucose concentration and counterregulatory hormones. This case report aims to describe the fluid management in a client with instability of blood glucose levels in DKA. A 42-year-old woman was rushed to the emergency room with decreased consciousness for 3 hours. Laboratory examination results: blood glucose >600mg/dL, Base Excess <-30mmol, urine ketones +3, urine protein +2, urine glucose +4, pH 6.8, HCO3 1.9mmol/L. The client had unstable blood glucose levels while in the treatment room. Fluid management was performed by combining 0.9% NaCl, WIDA 2A, 40% dextrose bolus, and continuous insulin drip, that was adjusted according to the client's blood glucose level. After receiving fluid management, the client's blood glucose levels are stable in the range of 100 - 200mg/dL on the fifth day until the client recovered. Providing fluid management tailored to the management of DKA and client needs can improve the stability of blood glucose levels so that this fluid management intervention can be utilized for DKA clients with similar complaints.